Value of electrocardiographic T wave inversion in lead aVL in prediction of Mid Left Anterior Descending Stenosis in patients with stable Coronary Artery disease - Magdy, Gehan; Yousef, Awad (Journal of Cardiology and Cardiovascular Medicine, 2017)
Background: The electrocardiogram (ECG) is a simple and noninvasive bedside diagnostic tool with a well-established role in the diagnosis of coronary artery disease (CAD). We aimed to study the diagnostic value of electrocardiographic ST-T wave changes in lead aVL in prediction of site of coronary artery stenosis in patients with chronic stable angina. Patients and Methods: study was conducted on 156 patients referred for invasive coronary angiography with history of stable CAD as proved by non- invasive tests, 12 lead ECG was recorded and fully interpreted with more focus on T wave direction in aVL lead. T waves in aVL were categorized into one of three groups: upright, flat or inverted. Results: regarding T wave in lead aVL, inverted T wave was reported in 71(45.5%) patients, 58 (37.2%) patients were with upright T wave in lead aVL and 27(17.3%) patients were with flat T wave in lead aVL, and we found that inverted T wave in lead aVL was most evident in 56(73.7%) patients with mid LAD with (highest κ value equal to 0.550[moderate agreement], and p value<0.001. Conclusions: This study confirmed the diagnostic value of T wave inversion in lead aVL in prediction of mid left anterior descending artery lesions in patients with stable coronary artery disease.